Core Muscle Training and Its Impact on Athletes' Explosive Power - Li, Guangye; Peng, Keshun (International Journal of Public Health and Medical Research, 2024)
Core training plays a vital role in modern athletic training and has a significant impact on an athlete's performance across a wide range of sports. The purpose of this article is to explore how core training can improve an athlete's explosive power and the specific contribution of this training method to athletic performance. Through literature review and empirical analysis, this study comprehensively evaluated the methods and effects of core muscle training and its application in different sports. The study found that systematic core muscle training significantly improved the athlete's stability, balance and power transfer efficiency, thereby enhancing their explosive power. This study provides athletes and coaches with scientific training guidance that can help them achieve better performance in competitive sports.